Peer review of the pesticide risk assessment of the active substance metribuzin - Álvarez, Fernando; Arena, Maria; Auteri, Domenica; Leite, Sofia Batista; Binaglia, Marco; Castoldi, Anna Federica; Chiusolo, Arianna; Cioca, Ana‐Andreea; Colagiorgi, Angelo; Colas, Mathilde; Crivellente, Federica; De Lentdecker, Chloe; et al. (EFSA journal, 2023)
The conclusions of the EFSA following the peer review of the initial risk assessments carried out by the competent authorities of the rapporteur Member State, Estonia, and co‐rapporteur Member State, Germany, for the pesticide active substance metribuzin and the assessment of application to amend existing residue definition are reported. The context of the peer review was that required by Commission Implementing Regulation (EU) No 844/2012, as amended by Commission Implementing Regulation (EU) No 2018/1659. The conclusions were reached on the basis of the evaluation of the representative use of metribuzin as a herbicide on potato and soybean (field use). The reliable end points, appropriate for use in regulatory risk assessment, are presented. Missing information identified as being required by the regulatory framework is listed. Concerns are reported where identified.